Impact of COVID-19 pandemic on continuing professional development of endodontists: A comprehensive survey study - Uslu, Gülşah; Özyürek, Taha; Kayahan, Mehmet Baybora; Gündoğar, Mustafa; Keskin, Neslihan Büşra (Türkiye Klinikleri, 2022)
Objective: Continuing professional development (CPD) is a lifelong process that continues despite all kinds of obstacles. The aim of this study was to evaluate of endodontists’ attitudes towards CPD during the coronavirus disease-2019 pandemic and online educa tional resources (OERs). Material and Methods: A questionnaire on demographic data and preferred resources before and after the pan demic was sent to 554 potential participants via e-mail. A chi-square test and multivariate logistic regression test were conducted on the ob tained data at a 5% significance level. Results: One hundred seventy five participants responded to the survey. Of all the participants, 67% were women and 45% were academicians. Since the pandemic began, OERs have been preferred over traditional resources, but traditional ones were considered more useful than OERs. Most of the respondents believed that contagion concerns represented the greatest obstacle to CPD. Gender and experience were related to the perception that the pandemic affected the respondents’ CPD activities (p<0.001). Spe cialty/PhD students tended to benefit more than others from OERs (p<0.05). The respondents mostly considered that OERs are comfort able and advantageous in terms of time, cost, professional knowledge and skill. Conclusion: The resources endodontists chose for CPD ac tivities seemed to have changed in favour of OERs during the pandemic despite their lower perceived usefulness as compared with traditional resources.

Amaç: Sürekli mesleki gelişim (SMG), her türlü engele rağ men yaşam boyu devam eden bir öğrenme sürecidir. Bu çalışmanın amacı, endodontistlerin koronavirüs hastalığı-2019 pandemisi sırasında SMG’ye ve online eğitim kaynaklarına (OEK) yönelik tutumlarını de ğerlendirmektir. Gereç ve Yöntemler: Beş yüz elli dört katılımcıya pandemi öncesi ve sonrası olmak üzere demografik veriler ve tercih edilen kaynaklar hakkında hazırlanmış bir anket e-posta yoluyla gön derildi. Elde edilen veriler üzerinde %5 anlamlılık düzeyinde ki-kare testi ve çok değişkenli lojistik regresyon analizi yapıldı. Bulgular: Yüz yetmiş beş katılımcı anketi cevaplamıştır. Tüm katılımcıların %67’si kadın ve %45’i akademisyendi. Pandemi başlangıcından itibaren OEK geleneksel kaynaklara tercih edilmiş, ancak geleneksel olanlar OEK’den daha kullanışlı kabul edilmiştir. Ankete katılanların çoğu, bulaş endişesini SMG’nin önündeki en büyük engel olarak görmüştür. Cinsiyet ve deneyim, pandeminin katılımcıların SMG faaliyetlerini et kilediği algısıyla ilişkili bulunmuştur (p<0,001). Uzmanlık/doktora öğ rencileri OEK’den daha fazla yararlanma eğiliminde bulunmuştur (p<0,05). Ankete katılanlar OEK’nin zaman, para, mesleki bilgi ve be ceri düzeyleri açısından rahat ve avantajlı olduğunu düşünmektedirler. Sonuç: Her ne kadar endodontistler pandemi döneminde SMG için OEK tercih etmiş olsalar da geleneksel kaynakları OEK’ye göre daha kullanışlı olduklarını düşünmektedirler.
COVID-19 pandemisinin endodontistlerin sürekli mesleki gelişimleri üzerine etkisinin etkisi: Kapsamlı bir anket çalışması
Keywords: COVID-19; Continuing Professional Development; Endodontics; Internet Usage; Online Resources; COVID-19; Sürekli Mesleki Gelişim; Endodonti; İnternet Kullanımı; Online Kaynaklar